It's A Square Problem!

Level pending

A semicircle is inscribed in square A B C D ABCD as shown above and B F BF is tangent to the semicircle at point E E .

Find B F A B \dfrac{BF}{AB} .


The answer is 1.25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let the length of each side of the square be 2 a 2a and the angle F B C \angle {FBC} be α α . Let the center of the semicircle be O O . Then D O F = 45 ° α 2 \angle {DOF}=45\degree-\dfrac{α}{2} . B E = A B = 2 a , E F = F D |\overline {BE}|=|\overline {AB}|=2a,|\overline {EF}|=|\overline {FD}| . Now tan ( 45 ° α 2 ) = F D O D tan ( α 2 ) = A B 2 F D A B + 2 F D \tan (45\degree-\dfrac{α}{2})=\dfrac{|\overline {FD}|}{|\overline {OD}|}\implies \tan (\dfrac{α}{2})=\dfrac{|\overline {AB}|-2|\overline {FD}|}{|\overline {AB}|+2|\overline {FD}|} , and tan α = C F A B = 1 F D A B \tan α=\dfrac{|\overline {CF}|}{|\overline {AB}|}=1-\dfrac{|\overline {FD}|}{|\overline {AB}|} . From these we get 3 tan 3 ( α 2 ) + 5 tan 2 ( α 2 ) + tan ( α 2 ) 1 = 0 tan ( α 2 ) = 1 3 tan ( 45 ° α 2 ) = 1 2 E F = F D = a 2 B F = B E + E F = 2 a + a 2 = 5 a 2 3\tan^3 (\dfrac{α}{2})+5\tan^2 (\dfrac{α}{2})+\tan (\dfrac{α}{2})-1=0\implies \tan (\dfrac{α}{2})=\dfrac{1}{3}\implies \tan (45\degree-\dfrac{α}{2})=\dfrac{1}{2}\implies |\overline {EF}|=|\overline {FD}|=\dfrac{a}{2}\implies |\overline {BF}|=|\overline {BE}|+|\overline {EF}|=2a+\dfrac{a}{2}=\dfrac{5a}{2} . Hence B F A B = 5 a 2 × 2 a = 5 4 = 1.25 \dfrac{|\overline {BF}|}{|\overline {AB}|}=\dfrac{5a}{2\times 2a}=\dfrac{5}{4}=\boxed {1.25}

Rocco Dalto
Mar 12, 2020

Let a a be the length of a side of the square A B C D ABCD .

( x a 2 ) 2 + y 2 = a 2 2 ( 2 x a ) 2 4 + y 2 = a 2 4 (x - \dfrac{a}{2})^2 + y^2 = \dfrac{a^2}{2} \implies \dfrac{(2x - a)^2}{4} + y^2 = \dfrac{a^2}{4} \implies

x 2 a x + y 2 = 0 y = x ( a x ) x^2 - ax + y^2 = 0 \implies y = \sqrt{x(a - x)}

m B E = x ( a x ) a x m = m P E = m_{BE} = \dfrac{\sqrt{x(a - x)} - a}{x} \implies m_{\perp} = m_{PE} = 2 x ( a x ) 2 x a = \dfrac{2\sqrt{x(a - x)}}{2x - a} =

x x ( a x ) a -\dfrac{x}{\sqrt{x(a - x)} - a} \implies 2 a x 2 x 2 2 a x ( a x ) = a x 2 x 2 2ax - 2x^2 - 2a\sqrt{x(a - x)} = ax - 2x^2 \implies

x = 2 x ( a x ) x 2 = 4 a x 4 x 2 x ( 4 a 5 x ) = 0 x = 2\sqrt{x(a - x)} \implies x^2 = 4ax - 4x^2 \implies x(4a - 5x) = 0 and x 0 x \neq 0

x = 4 a 5 y = 2 a 5 \implies x = \dfrac{4a}{5} \implies y = \dfrac{2a}{5}

Using E : ( 4 a 5 , 2 a 5 ) E:(\dfrac{4a}{5}, \dfrac{2a}{5}) and B : ( 0 , a ) m B E = 3 4 B:(0,a) \implies m_{BE} = -\dfrac{3}{4} \implies y = 3 4 x + a y = -\dfrac{3}{4}x + a

Using line x = a y = a 4 x = a \implies y = \dfrac{a}{4} and using F : ( a , a 4 ) F:(a,\dfrac{a}{4}) and B : ( 0 , a ) B:(0,a) \implies

B F = 25 a 2 16 = 5 4 a \overline{BF} = \sqrt{\dfrac{25a^2}{16}} = \dfrac{5}{4}a \implies B F A B = 5 4 = 1.25 \dfrac{\overline{BF}}{AB} = \dfrac{5}{4} = \boxed{1.25}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...